Planning for optimal performance - What happens before the taper? - Johns, K. L.; Philipson, P. M.; Hayes, P. R. (International Journal of Sports Science & Coaching, 2019)
This study analysed the contemporary performance data of middle-distance athletes to determine (a) the number of competitive performances prior to the season`s fastest performance and (b) the time frame between their first and fastest competitive performances of that season. Using a publicly available database, data on the number of races and days between athletes first and fastest races were extracted. The analysis utilised 4800 observations from 1166 individual athletes for the period 2006-2017. Male 800 m athletes achieved their fastest performance in eight races (IQR = 4-12) distributed over 55 days (IQR = 29-87). Female 800 m athletes also required eight races (IQR = 5-12), distributed over 63 days (IQR = 34-91). In the 1500 m event, male athletes, required six races (IQR = 3-9) over 48 days (IQR = 25-76), while female athletes, required seven races (IQR = 4-10) over 56 days (IQR = 28-84). For both sexes, 1500 m athletes raced less and over a shorter period than 800 m athletes before reaching their fastest performance. Female athletes had a longer time frame and number of races than male athletes. This study provides an evidence-based indicator of when a middle-distance runner`s fastest performance is likely to occur, providing benchmarks that could act as a guide for coaches when designing competition programmes, prior to any tapering process.